Pengaruh Model Pembelajaran Cooperative Learning Tipe Stad Berbantuan Media Diorama 3D Terhadap Kemampuan Kolaborasi Siswa Kelas V SDN Pancuran - Dien Madina Farinada; Anna Maria Oktaviani; Sastra Wijaya (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF THE STAD-TYPE COOPERATIVE LEARNING MODEL ASSISTED BY 3D DIORAMA MEDIA ON THE COLLABORATION ABILITY OF CLASS V STUDENTS OF SDN PANCURAN This study aims to determine the effect of the Cooperative Learning model of the Student Teams Achievement Division (STAD) type assisted by 3D diorama media on the collaboration ability of fifth-grade students at SDN Pancuran. The background of this research is the low collaboration ability of students, indicated by passive participation, unequal task sharing, and lack of mutual assistance during group discussions. The method used in this study is a quantitative approach with a quasi-experimental design. The research population includes all fifth-grade students, with sampling conducted through purposive sampling. Data collection techniques utilize observation sheets, questionnaires, and documentation. The results show a significant positive effect of the STAD model assisted by 3D diorama media on students' collaboration abilities. There is a notable difference in collaboration skills before and after the implementation of this learning model. Furthermore, students responded very positively to the integration of 3D dioramas in science learning, particularly on the food chain topic. In conclusion, combining the STAD model with 3D diorama media effectively creates an interactive, meaningful, and collaborative learning atmosphere for elementary students.